Ang Bagong Pinoy : an ethical framework for the new Filipino - Boydon, Ernersto "Boogie" C. (Penablanca, Cagayan : John 14-14 Books Publishing Center, 2023)
This book is about a quest for a moral compass for the Filipino people.
About the Book Cover -- How this books came about -- About ang Bagong Pinoy -- On Change and the Need for Unity -- What is Ethics? -- Ethics vs. Morals -- Right vs. Wrong -- The Anatomy of Temptation -- Ethical Frameworks -- Ethical Dilemmas -- Faith-based Ethics -- Charity vs, Egocentricity -- Ethics as faith in Action -- Ethics and Excellence -- A Hierarchy of Vakues -- The ICE Paradigm -- An Ethical Framework for the New Filipino -- Ang Bagong Pinoy Begins in the Home -- Loving our Neighbor is at the Heart Rebuilding our Nation -- Ako ay Pilipino -- Conclusion -- Notes, References and Attributions.
Includes bibliographical references.